Conflict and child mortality in Mali: A synthetic control analysis - Masset, Edoardo (International Food Policy Research Institute, 2021)
A civil conflict broke out in northern Mali in 2012, which is continuing to the present day. Very little is known about its impact on civilians. In this paper we show how to use birth history data to build long time series of mortality rates, and we use novel synthetic control methods to estimate the impact of the Malian civil conflict on child mortality. We find that conflict produced a significant increase in under-5 mortality, and that the impact was negligible on infant mortality but large on child mortality. We analyse trends of key mortality determinants, and conclude that a reduction in vaccination rates and in access to health care in childhood were the most likely mediators of impact. Northern Mali is today one of the poorest and most neglected areas of the world where humanitarian assistance is urgently needed.